Hadith #3641 - Sunan Abi Dawud - Abu al-Darda; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Uthman bin Abi Swd'h عثمان بن أبي سودة المقدسي (Sunan Abi Dawud)
Kathir ibn Qays said: I was sitting with AbudDarda’ in the mosque of Damascus. A man came to him and said: AbudDarda, I have come to you from the town of the Messenger of Allah (ﷺ) for a tradition that I have heard you relate from the Messenger of Allah (ﷺ). I have come for no other purpose. He said: I heard the Messenger of Allah (ﷺ) say: If anyone travels on a road in search of knowledge, Allah will cause him to travel on one of the roads of Paradise. The angels will lower their wings
Grade: Sahih